2024
DOI: 10.1007/s12012-024-09843-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Machine Learning Algorithms to Predict 1-Year Ischemic Stroke and Bleeding Events in Patients with Atrial Fibrillation and Cancer

Bang Truong,
Jingyi Zheng,
Lori Hornsby
et al.

Abstract: In this study, we leveraged machine learning (ML) approach to develop and validate new assessment tools for predicting stroke and bleeding among patients with atrial fibrillation (AFib) and cancer. We conducted a retrospective cohort study including patients who were newly diagnosed with AFib with a record of cancer from the 2012–2018 Surveillance, Epidemiology, and End Results (SEER)-Medicare database. The ML algorithms were developed and validated separately for each outcome by fitting elastic net, random fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
2
1
0
Order By: Relevance
“…Furthermore, the HAS-BLED score’s reliance on labile INR is outdated, given the shift towards DOACs 13 . Our findings of a modest improvement in ML performance over conventional risk scores align with prior studies 16,17 , which consistently demonstrated the poor performance of the HAS-BLED score, with AUC-ROC ranging from 0.50 to 0.64 16,19,20,44,45 . However, these studies were limited by their focus on broader contexts or specific AF subpopulations 18,19 , restricting their applicability to the broader AF population on DOACs in a real-world clinical scenario when first evaluated by a cardiologist for AF management.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the HAS-BLED score’s reliance on labile INR is outdated, given the shift towards DOACs 13 . Our findings of a modest improvement in ML performance over conventional risk scores align with prior studies 16,17 , which consistently demonstrated the poor performance of the HAS-BLED score, with AUC-ROC ranging from 0.50 to 0.64 16,19,20,44,45 . However, these studies were limited by their focus on broader contexts or specific AF subpopulations 18,19 , restricting their applicability to the broader AF population on DOACs in a real-world clinical scenario when first evaluated by a cardiologist for AF management.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings of a modest improvement in ML performance over conventional risk scores align with prior studies 16,17 , which consistently demonstrated the poor performance of the HAS-BLED score, with AUC-ROC ranging from 0.50 to 0.64 16,19,20,44,45 . However, these studies were limited by their focus on broader contexts or specific AF subpopulations 18,19 , restricting their applicability to the broader AF population on DOACs in a real-world clinical scenario when first evaluated by a cardiologist for AF management. It is worth noting that in the original HAS-BLED publication, the AUC for the derivation cohort was 0.72, and for the validation cohort, it ranged from 0.50 to 0.67 among patients on warfarin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation